The Impact of Palm Oil Production and Islamic Financial Behavior on Farmers’ Welfare: the Moderating Role of Sharia Finance Literacy - Aldino, Imam; Nurlaila, Nurlaila; Yanti, Nursantri (IAIN Manado, 2025)
This study investigates the impact of palm oil production and Islamic financial behavior on farmers' welfare in Rantau Utara District, Labuhan Batu Regency, with Islamic financial literacy as a moderating variable. The study aims to bridge the gap between rising palm oil production levels and the persistent welfare disparities experienced by smallholder farmers, emphasizing the crucial role of financial literacy in translating Islamic economic values into effective financial management. A quantitative approach with purposive sampling was used for 85 respondents, and the data were analyzed using multiple linear regression and moderated regression analysis (MRA) to examine the relationships among variables. This method was chosen because it allows for identifying the direct influence of independent variables (palm oil production and Islamic financial behavior) on the dependent variable (farmers' welfare), as well as testing the moderating role of Islamic financial literacy. The results show that palm oil production has a significant positive effect on farmers' welfare (t = 6.633; p < 0.05), while Islamic financial behavior alone does not significantly influence welfare (p > 0.05). However, Islamic financial literacy significantly moderates and strengthens this relationship (p = 0.018), increasing the model's explanatory power from 35.1% to 41.7%. These findings highlight the importance of integrating Islamic financial literacy into rural development policies to enhance farmers' economic resilience and promote inclusive, sharia-compliant growth in Indonesia’s agricultural sector.